Processing mechanism of electrical discharge-assisted milling titanium alloy based on 3D thermal-mechanical coupling cutting model. (June 2022) - Li, Changping; Huang, Lei; Xu, Moran; Chen, Yini; Chen, Jielin; Li, Shujian; Li, Pengnan; Choi, Young-Soo; Ko, Tae Jo
Abstract: Electrical discharge-assisted milling (EDAM) is an efficient method for processing titanium alloys, but the processing mechanism of EDAM titanium alloy is not completely understood. Therefore, in this study, a thermal-mechanical coupling cutting model was established to examine the processing mechanism of EDAM. The thermal-mechanical coupling model included a random discharge model and a cutting model with a temperature field. The temperature field of the workpiece after discharge and before cutting was clarified. Based on the high-temperature hardness test results of the titanium alloy and modified layer after discharge, increasing the temperature can effectively reduce their material hardness. In addition, the material removal process and chip formation mechanism in EDAM and conventional milling (CM) were studied. The variation laws of the cutting force, stress, and cutting temperature under two cutting methods are discussed. A verification experiment showed that the cutting force was in good agreement with the simulation results. Moreover, EDAM can effectively reduce the cutting force, as well as the stress distribution on the surface of the workpiece. These results can provide an important reference for EDAM to formulate the machining parameters.